2008
DOI: 10.5194/acp-8-813-2008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term climatology of air mass transport through the Tropical Tropopause Layer (TTL) during NH winter

Abstract: Abstract.A long-term climatology of air mass transport through the tropical tropopause layer (TTL) is presented, covering the period from 1962-2005. The transport through the TTL is calculated with a Lagrangian approach using radiative heating rates as vertical velocities in an isentropic trajectory model. We demonstrate the improved performance of such an approach compared to previous studies using vertical winds from meteorological analyses. Within the upper part of the TTL, the averaged diabatic ascent is 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…The difference in the distribution of the position of minimum saturation mixing ratios between kinematic and diabatic ERA-Interim trajectories induces only minor differences in model predicted entry mixing ratios (see also Liu et al, 2010). In agreement with previous work (Krüger et al, 2008) we find that the patterns of distribution of minimum saturation mixing ratio of TST-trajectories (Bonazzola and Haynes, 2004;Kremser et al, 2009) are a robust feature of TST.…”
Section: The Difference Between Water Vapour and Ozone As Transport Tsupporting
confidence: 90%
“…The difference in the distribution of the position of minimum saturation mixing ratios between kinematic and diabatic ERA-Interim trajectories induces only minor differences in model predicted entry mixing ratios (see also Liu et al, 2010). In agreement with previous work (Krüger et al, 2008) we find that the patterns of distribution of minimum saturation mixing ratio of TST-trajectories (Bonazzola and Haynes, 2004;Kremser et al, 2009) are a robust feature of TST.…”
Section: The Difference Between Water Vapour and Ozone As Transport Tsupporting
confidence: 90%
“…Any later breakdown of species can only change the stratospheric balance between species but not the total budgets of e.g., halogens or sulfur. It has been shown that most air masses reach their LCP above the West Pacific (Fueglistaler et al, 2004;Bonazzola and Haynes, 2004;Krüger et al, 2008) and we will show here that the source region in the boundary layer and the transit region in the troposphere are also situated in the same region.…”
Section: Introductionsupporting
confidence: 54%
“…By assuming that this gap is significant, additional processes may come into the focus of stratospheric bromine research, i.e., the seasonality and possibly long-term trend of the bromine transported into the stratosphere (e.g., Levine et al, 2008;Krüger et al, 2008;Fueglistaler et al, 2009;Schofield et al, 2011;Ploeger et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Here one may wonder whether (a) this result is significant, (b) some Br inorg y is actually removed by heterogeneous processes in the TTL (e.g., Aschmann et al, 2011;Aschmann and Sinnhuber, 2013), or (c) TTL Br y shows some seasonality analogous to the "tape recorder" for H 2 O (e.g., Levine et al, 2008;Krüger et al, 2008;Fueglistaler et al, 2009;Schofield et al, 2011;Ploeger et al, 2011).…”
Section: Uncertainties In Estimating the Inorganic Bromine Partitioningmentioning
confidence: 99%